Clinical Outcome of Eradication Therapy for Gastric Mucosa-Associated Lymphoid Tissue Lymphoma according to H. pylori Infection Status - Ju Seok Kim; Sun Hyung Kang; Hee Seok Moon; Jae Kyu Sung; Hyun Yong Jeong (Gastroenterology Research and Practice)
Background. To evaluate the long-term outcome of H. pylori eradication therapy for gastric MALT lymphoma according to the presence of H. pylori infection. Methods. We retrospectively reviewed the medical records of patients between January 2001 and June 2014. The clinicopathologic characteristics and clinical outcomes were compared between H. pylori-positive and H. pylori-negative gastric MALT lymphoma groups. Results. Fifty-four patients were enrolled: 12 H. pylori-negative and 42 H. pylori-positive patients. The tumor was located more frequently in both the proximal and distal parts of the stomach (P=0.001), and the percentage of multiple lesions was significantly greater in the H. pylori-negative group (P=0.046). Forty-seven patients received initial eradication therapy, and 85% (35/41) of H. pylori-positive patients and 50% (3/6) of H. pylori-negative patients achieved complete remission after eradication therapy. The presence of multiple lesions was a predictive factor for unresponsiveness to H. pylori eradication (P=0.024). The efficacy of eradication therapy (P=0.133), complete remission (CR) maintenance period, and relapse after eradication therapy were not significantly different between the two groups. Conclusions. H. pylori eradication therapy could be an effective first-line treatment for localized H. pylori-negative gastric MALT lymphoma, especially for single lesions.